Etiological Agents of Bacteraemia and Antibiotic Susceptibility Pattern of Isolates in Kathmandu Model Hospital, Kathmandu - Amatya, Niroj Man; Shrestha, B.; Lekhak, B. (Journal of Nepal Health Research Council, 2009)
Not uploaded. Key words: Bactaremia; Ciprofloxacin; Salmonella; Antibiotic pattern DOI: 10.3126/jnhrc.v5i2.2450 Journal of Nepal Health Research Council (JNHRC) Vol. 5, No.2, October 2007 5-12